Penerapan Just In Time Dalam Meningkatkan Efektivitas Dan Efisiensi Produksi (Suatu Studi Pada PT Albasi Priangan Lestari Kota Banjar) - Idam Wahyudi; Enas Enas; Iwan Setiawan (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2023)
This research is focused on the Application of Just In Time in Increasing Production Effectiveness and Efficiency (A Study at PT Albasi Priangan Lestari, Banjar City). The problems encountered in this study include: 1]. How is the application of just in time in increasing the effectiveness and efficiency of production at PT Albasi Priangan Lestari?; 2]. What are the obstacles encountered in implementing just in time at PT Albasi Priangan Lestari?; 3]. What are the solutions to overcome obstacles in implementing just in time at PT Albasi Priangan Lestari?; The purpose of this study: 1]. To find out the application of just in time at PT Albasi Priangan Lestari; 2]. To find out what obstacles are faced in implementing just in time at PT Albasi Priangan Lestari; 3]. To find out how the solution to overcome obstacles in implementing just in time at PT Albasi Priangan Lestari. The method used in this research is descriptive qualitative research method. Meanwhile, to analyze the data obtained used descriptive analysis techniques. The results of the study show that the application of just in time in increasing production effectiveness and efficiency at PT Albasi Priangan Lestari is carried out by: close communication with suppliers. Then Closeness of Communication with Customers. Furthermore, Responsiveness in Information Change. Accuracy of Executing Schedule. As well as the ability to reduce costs. Barriers to implementing just in time to increase production effectiveness and efficiency come from supporting tools for mobilizing materials and goods such as forklifts, dump turcks and losbak, supply of electrical energy and shipping costs. The solution to overcome these obstacles is to equip supporting equipment such as handlifts. Meanwhile, to handle the supply of electricity, the company built two power substations.